(untitled) (Web of Scientists and Scholars: Journal of Multidisciplinary Research, 2024)
The pandemic of the new coronavirus infection (COronaVIrusDisease 2019) COVID-19 and the quarantine measures that followed it, in particular, the self–isolation of the population, have left a serious imprint on the lifestyle of people, especially those suffering from chronic non-communicable diseases (CNID). First of all, this could affect the quality of the therapy they constantly take. For certain reasons, during the COVID-19 pandemic, such patients could have a number of problems with contacting the appropriate specialist doctor, receiving or purchasing medications they constantly take (LP). A number of recently published studies have reported the occurrence of such problems in dermatological patients, in patients with autoimmune inflammatory rheumatic diseases. The aim of the present study was to find out how the adherence to constant therapy has changed in patients with chronically stable coronary artery disease (CHD) in self-isolation during the COVID19 pandemic.